Measuring Teacher Professional Development Learning Activities in Post Covid-19 - Nasrullah Nasrullah; Elsa Rosalina; Nanik Mariani; Sa'da Kamalia (Alsuna: Journal of Arabic and English Language, 2021)
Purpose - To fill the void, this study comes with the aim of finding out perception which underpins the extent to which activities have fulfilled the teachers’ need of their development through Teachers’ Forum (MGMP) or not, amid post-Covid-19 at this moment. Design/methodology/approach - This study employed a qualitative approach by using an open-ended questionnaire and recruiting 25 in-service teachers. Findings - The finding of this study revealed that most the in-service teachers have their positive view to excel their professional development, especially with regard to making clear of learning aims, widening up the horizon to provide sufficient materials many resources, adding knowledge and skills in pedagogical strategies, and strengthening ability in selecting appropriate assessment in the activities conducted by MGMP. Originality/value - The implication of this study calls for the inclusion of in-service teachers to always be open-minded, self-reflected, and willing to learn a new thing to ensure effective instructional practices Paper type – Research Paper